Computational solutions of conformable space-time derivatives dynamical wave equations: Analytical mathematical techniques - Asghar Ali; Aly R. Seadawy; Dumitru Baleanu (Results in Physics, 2020)
In this article, the instigator sets up the profuse traveling wave solutions four types of fractional nonlinear equations in the sense of conformable derivatives by using the novel form of modified mathematical technique. The constructed traveling wave solutions are articulated in terms of trigonometric, hyperbolic and exponential functions. The derived results are fruitful for the physical demonstrations of problems in mathematical physics and engineering.